2010
DOI: 10.1021/je901011c
|View full text |Cite
|
Sign up to set email alerts
|

Improved Isotherm Data for Adsorption of Methane on Activated Carbons

Abstract: This article presents the adsorption isotherms of methane onto two different types of activated carbons, namely, Maxsorb III and ACF (A-20) at temperatures from (5 to 75)°C and pressures up to 2.5 MPa. The volumetric technique has been employed to measure the adsorption isotherms. The experimental results presented herein demonstrate the improved accuracy of the uptake values compared with previous measurement techniques for similar adsorbate-adsorbent combinations. The results are analyzed with various adsorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
49
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(55 citation statements)
references
References 23 publications
6
49
0
Order By: Relevance
“…5 shows the results on the BET plot. It is observed that the present specimen possesses surface area about 3311 m 2 /g and the figure agrees well with the published data [27,30,32].…”
Section: Surface Characteristics Analysissupporting
confidence: 92%
“…5 shows the results on the BET plot. It is observed that the present specimen possesses surface area about 3311 m 2 /g and the figure agrees well with the published data [27,30,32].…”
Section: Surface Characteristics Analysissupporting
confidence: 92%
“…1(b). The detailed surface characteristics of Maxsorb III and the adsorption parameters for methane/Maxsorb III pair are reported by Loh et al 14 . The stainless steel mesh (500 holes per inch) is wrapped around the heat exchanger to hold the activated carbon (AC) sample as shown in Fig.…”
Section: Brief Description Of the Experimental Apparatusmentioning
confidence: 98%
“…4 shows the amount of adsorbed mass in the AC bed during the charge process. The adsorbed mass for the experimental operating conditions are evaluated using the adsorption parameters for methane/Maxsorb III pair reported by Loh et al 14 . It can be seen that the AC bed attains its maximum capacity of gas adsorption within 10 minutes of the charge period when water is circulated to remove the heat of adsorption.…”
Section: Charge Processmentioning
confidence: 99%
“…The plot has been calculated using the data published in [3]. It is clearly visible that in investigated pressure range (up to 30 atm) ANG has higher storage potential than CNG.…”
Section: Adsorbed Natural Gas and Comparison With Other Gas Storage Mmentioning
confidence: 99%